Resilience in a Digital Age: Global Challenges in Organisations and Society - Matos, F.; Selig P. M.; Henriqson, E. (2022)
In recent years, decision-makers from all sectors have been using 'resilience' as a keyword for managing societal turbulences. But what is resilience? How can we benefit from integrating digital transformation and resilience? In this book, some of the world's leading experts on resilience explore the issue and discuss possible answers to these questions. The editors of this book believe that resilience is the master key for the future. However, they also remind us that people are at the base of any process of resilience and, only by placing people at the center of transformation, can we aspire to have resilient organizations and a resilient society.